2006
DOI: 10.1074/jbc.m602956200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mn2+-binding Aspartates from α, β, and γ Subunits of Human NAD-dependent Isocitrate Dehydrogenase

Abstract: The human NAD-dependent isocitrate dehydrogenase (IDH), with three types of subunits present in the ratio of 2␣:1␤:1␥, requires a divalent metal ion to catalyze the oxidative decarboxylation of isocitrate. With the aim of identifying ligands of the enzyme-bound Mn 2؉ , we mutated aspartates on the ␣, ␤, or ␥ subunits. Mutagenesis target sites were based on crystal structures of metal-isocitrate complexes of Escherichia coli and pig mitochondrial NADP-IDH and sequence alignments. Aspartates replaced by asparagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Ser Ͻ Phe Ͻ Glu) suggests that the same properties determine the allosteric effect of ADP on the enzyme. Previous studies have shown that mutations at other positions in the ␤ subunit resulted in a higher K m for NAD and complete or partial loss of allosteric activation by ADP (6,15,16,19). None of these studies showed a major effect on the V max of the enzyme.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Ser Ͻ Phe Ͻ Glu) suggests that the same properties determine the allosteric effect of ADP on the enzyme. Previous studies have shown that mutations at other positions in the ␤ subunit resulted in a higher K m for NAD and complete or partial loss of allosteric activation by ADP (6,15,16,19). None of these studies showed a major effect on the V max of the enzyme.…”
Section: Discussionmentioning
confidence: 71%
“…All the mutants of IDH, except the ␥Y135F and ␣Y126E, were purified using the established protocol described by Soundar et al (15,16). As assessed by SDS-PAGE (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations